First isolation of Vibrio vulnificus causing sepsis in Santa Catarina, Brazil Isolation of Vibrio vulnificus in Brazil - Batista, Bruna Gerardon; Júnior, Sidnei Alves dos Santos; Aquino, Alzira Resende do Carmo; Argenta, Rodrigo (Clinical and Biomedical Research, 2016)
Vibrio vulnificus is a bacterium present in natural marine environments that causes infections in immunocompromised people. Sepsis in humans caused by this microorganism is usually accompanied by bullous skin lesions. In the present study we report a case of infection caused by this bacterium affecting a diabetic man, 74 years old, who fell overboard and hurt his leg. The identification of the V. vulnificus was made in the blood culture sample. This is the first report of isolation of V. vulnificus in Santa Catarina, Brazil, showing the dissemination of this bacterium in warm seawater over the world. Keywords: Vibrio vulnificus; infection; immunocompromised; seawater